Analisis Konsep “Damai Sejahtera yang Melampaui Akal” dalam Filipi 4:6–7 sebagai Konsep Psikologis dalam Mengatasi Kecemasan - Disyon Arie Saldy Laja; Veronika Resta; Felix Munda (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
Anxiety is one of the most prevalent psychological problems globally, yet approaches integrating spiritual dimensions remain underexplored. This study analyzes the concept of "peace that surpasses all understanding" in Philippians 4:6-7 as a psychological construct for addressing anxiety. Using hermeneutical exegesis method, this research examines the textual meaning and psychological dimensions of this concept within modern psychological theory frameworks. The findings reveal that divine peace differs from conventional psychological approaches through three key aspects: it represents an active positive psychological condition rather than mere absence of anxiety, operates through relational mechanisms with God that transcend rational cognitive processes, and integrates prayer, supplication, and thanksgiving as holistic spiritual-psychological coping strategies. The concept of "guarding heart and mind" demonstrates a dual protective mechanism maintaining both affective and cognitive stability simultaneously. This study contributes to developing more holistic psychological theory integrating spiritual dimensions and more effective counseling practices for anxiety management in Christian contexts.